2019
DOI: 10.32598/hdq.4.3.157
|View full text |Cite
|
Sign up to set email alerts
|

Presenting a Model for Telemedicine in Earthquake for Iran

Abstract: Iran is a country with a high rate of natural disasters like earthquake. The environmental conditions slow down the delivery of health services, especially in the event of disasters. The modern technologies such as telemedicine are appropriate for facilitating disaster relief operations after an earthquake. This study aimed to develop a model for the implementation of telemedicine in an earthquake. Materials and Methods: The study was carried out using a mixed-methods research in three phases: 1. Review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…All countries try to control the extent of the epidemic and the resulting mortality [9]. The experience of previous studies has shown that the existence of a reliable and sufficient system in the prehospital emergency in response to health emergencies, especially the urgency of infectious diseases, is necessary [10,11]. The role of prehospital emergency preparedness in controlling infectious diseases, especially emerging types, was studied by Faraq and associates.…”
Section: Introductionmentioning
confidence: 99%
“…All countries try to control the extent of the epidemic and the resulting mortality [9]. The experience of previous studies has shown that the existence of a reliable and sufficient system in the prehospital emergency in response to health emergencies, especially the urgency of infectious diseases, is necessary [10,11]. The role of prehospital emergency preparedness in controlling infectious diseases, especially emerging types, was studied by Faraq and associates.…”
Section: Introductionmentioning
confidence: 99%